Penerapan Model Think Talk Write untuk Meningkatkan Keterampilan Menulis Kalimat Efektif Siswa Sekolah Dasar - Erlina Sari; Iis Aprinawati; Rizki Ananda (Edumaspul: Jurnal Pendidikan, 2021)
Abstract This research was motivated by the low skill of writing effective sentences in the third grade thematic learning at SDN 005 Padang Luas, Tambang District, Kampar Regency. One solution to overcome this problem is to apply themodel Think Talk Write. The purpose of this study was to improve effective sentence writing skills in third grade students of SDN 005 Padang Luas. This research method is classroom action research which is carried out in two cycles.The subjects of this research were class III students, totaling 17 students with 9 male students and 8 female students. Data collection techniques are tests, observations, documentation. The results of this study can be concluded that in the first cycle is classified as good with an average of 67.82, then out of 17 students only 8 students completed and classical completeness 47.05%. In cycle II it was very good with an average of 77.47 then from 17 students there were 14 students who completed and for classical completeness 82.35%. Thus, it can be concluded that the application of themodel Think Talk Write (TTW) can improve effective sentence writing skills in class III SDN 005 Padang Luas. Keywords: Model Think Talk Write (TTW), writing skills, effective sentences, Elementary School Students